Compliance with gluten free diet in coeliac disease. Issue 7 (July 1987) - Colaco, J; Egan-Mitchell, B; Stevens, F M; Fottrell, P F; McCarthy, C F; McNicholl, B
Abstract : Fifty two children in whom coeliac disease was confirmed by persistent enteropathy while they were taking gluten were monitored to assess the effects of compliance with a gluten free diet (GFD). Between the ages of 17.8 and 18.5 years height (in 45 patients followed up for a mean of 14.9 years) and weight (in 43 followed up for a mean of 15.2 years) were significantly lower in those complying poorly with a GFD compared with those complying well. Of the 37 patients still attending the clinic after a mean of 25 years, having been followed up for a mean of 18.4 years, 16 who had complied well with the diet had normal or only slightly abnormal mucosal morphology whereas all 10 who had not complied had abnormal morphology. In these 10 lactase, sucrase, and alkaline phosphatase activities were significantly less than values in those who complied well. Mucosal sucrase and alkaline phosphatase activities in those who complied well were no different from those in a control population, whereas lactase activity was significantly lower. It is concluded that failure to comply with a GFD during childhood results in decreased adult stature and in persisting active enteropathy with depressed brush border enzyme activity.